The Role of Roscoe Pound's Social Engineering Theory in Realizing Social Justice Through Legal Discovery in Indonesia - Triana, Yeni; Hartono, Wandi; Setiawan, Jetmiko; Muhardi, Dekky (Raudhah Publisher, 2024)
Roscoe Pound, a well-known legal expert from the United States, said The theory of